Induction of Prophage SPO2 in Bacillus subtilis: Prophage Excision in the Absence of Bacterial or Bacteriophage DNA Synthesis - Arwert, Fré (1974)
Bacillus subtilis lysogenic for SPO2 wild type was induced under conditions preventing synthesis of both bacterial and phage DNA. The infectivity of phage DNA in transfection is strongly decreased under these conditions, whereas the activity of single phage genes as measured by marker rescue with superinfecting phage is unaffected. DNA from induced cells was sedimented in neutral sucrose gradients. After induction, phage DNA was detected at a position in the gradients, which was different from the bulk of the bacterial DNA, corresponding to linear double-stranded DNA of about 25 × 10(6) daltons. Similar results were obtained with bacteria lysogenic for a SPO2 prophage carrying a DNA-negative mutation. No separation of phage and bacterial DNA activity was detected when chloramphenicol was present during the induction period. These experiments show that prophage SPO2 can excise from the bacterial chromosome without previous replication.